Beverage consumption in Auckland primary school children : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics at Massey University, Albany, New Zealand - Smirk, Emma (Massey University, 2019)
Background: The New Zealand (NZ) Ministry of Health advises that plain water and plain low-fat milk should be consumed daily and that if children are to drink sugar-sweetened beverages (SSB) they should be limited. The latest comprehensive NZ beverage intake data in 8 to 12 year old children was published in 2008, however, fizzy drink intake data is updated annually. This means that NZ is lacking a full picture of children’s beverage consumption. SSB intake has been associated with weight gain in some studies. However, most of these studies calculate adiposity using body mass index (BMI) and few measure body fat percentage (BF%). International and limited national evidence has identified home availability, parental encouragement, socioeconomic status, and knowledge in children as factors associated with SSB intake. Many NZ schools have become ‘water-only’ schools (WOS) to try to reduce SSB consumption. Aim: To investigate beverage consumption in 8 to 12 year old Auckland primary school children. Methods: This cross-sectional study evaluated beverage intake and associated factors using self-administered questionnaires. SSB consumption measurements consisted of 17 types of beverages, and different combinations of these. Body composition was measured using bioelectrical impedance analysis (BIA). Chi squared and Mann-Whitney tests were used to examine the associations between SSB consumption and the factors associated with it. Results: Children (n=695, 9.9±0.7 years, 44.8% male) were recruited from 6 schools (4 WOS). Plain water and plain milk were consumed less than once per day by 11.6% and 54.7% of the children, respectively. Soft drink and fruit juice were consumed more than once per week by 30.6% and 39% of the children, respectively. SSBs (p<0.001), including fruit juice (p=0.021), had a positive relationship with BF% in girls. There was an increased likelihood of consuming beverages at least once per week if they were usually available at home. Receiving a lot of encouragement for healthy beverage intake from parents or school had an inverse relationship with SBB intake (p<0.001). Low socioeconomic status was inversely associated with SSB intake (p<0.001). WOS had a higher consumption of SSBs compared to non-WOS (p<0.001). Conclusions: Too many children in this cohort were not meeting the NZ Ministry of Health recommendations for plain water and milk consumption. Thus, they may benefit from increasing their intake, whilst decreasing their SSB intake. If parents limited SSB home availability and encouraged intake of healthy beverages it may contribute to a decrease in their children’s SSB consumption. Our findings support a recommendation to include fruit juice in any public health actions to discourage SSB consumption. More research is needed to assess school water-only policies and their effect on SSB consumption.
Keywords: School children; Nutrition; New Zealand; Auckland; Beverages; Soft drinks; Fruit juices; children; obesity; sugar sweetened beverages; home; school